Life at Maripaston - Ziel de, H. (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 1973)
The Matawai Maroon Johannes King (ca. 1830-1898) taught himself to read and write at an advanced age. He wanted to bridge the gap between the generations by publishing his Book of Horrors (Skrekiboekoe) and the present book which has been given the title Life at Marispaston. King wanted to explain the root of the problems between him and his elder brother, Chief Noah Andrai, representatives respectively of the church and the state at the village level. King wanted to justify his life in the eyes of the church, the EBG-Moravian Brethren, and his fellow Maroons. This book is an important contribution to the church history of Suriname, yet also offers insights into the history of the Maroon communities in Suriname. This book is one of the first original works in Sranantongo.